Towards a Contemporary Philosophy of Islamic Science - Anwar Ibrahim (International Institute of Islamic Thought, 1990)
Our understanding of science itself as a body of knowledge and as a system of analysis and research has changed over the last decades, just as over the last two centuries, or especially after the age of Enlightement in Europe, science has become more powerful, more sophisticated and complex. It is rather difficult to determine where science ends and where technology begins. In fact there is a gmwing awareness that the physical or nam sciences, as a means of studying and understanding nature, are relying on the more “humanistic“ and cultural approaches adopted by the social sciences or the humanities. The tradition of natural science is being challenged by new discoveries of the non-physical and non-natural sciences which go beyond the physical world. Certainly research is vital for the growth and development of all sciences that attempt to discover and understand the “secrets” of nature. The validity of any scientific theory depends on its research and methodological premises and even that-its proposition or theories (in the words of a leading cosmologist and theoretical physicist, Stephen Hawking) -is tentative. Hawlung says: “Any physical theory is always provisional, in the sense that it is only a hypothesis: you can never prove it. No matter how many times the results of experiments agree with some theory, you can never be sure that the next time the result will not contradict the theory. On the other hand, you can disprove a theory by finding even a single observation that disagrees with the predictions of the theory.” The history of Western science is rooted in the idea of finding the ’truth’ by objectivity. Nothing can be believed until there is a scientific proof of its existence, or until it can be logically accepted by the rational mind. The classical scenario of scientific work gives you an austere picture of heroic activity, undertaken against all odds, a ceaseless effort to subjugate hostile and menacing nature, and to tame its formidable forces. Science is depicted ...